Illuminating Cassiopea jellyfish: biochemical revelations from metabolism to coloration under ultraviolet A and photosynthetically active radiation - Samir M. Aljbour; Samir M. Aljbour; Susana Agustí (Frontiers in Marine Science)
Sunlight, including ultraviolet (UVA and UVB) and photosynthetically active radiation (PAR), is vital for the physiology of invertebrates with symbiotic Symbiodiniaceae. While the effects of UVB and PAR are well-studied, the impact of UVA remains underexplored. This study investigates the effects of varying UVA and PAR intensities on the metabolic, oxidative, and photosynthetic responses of Cassiopea andromeda jellyfish. Over 18 days, 24 medusae were exposed to four light treatments: low PAR (± low UVA) and high PAR (± high UVA). Results showed significant increases in jellyfish mass and umbrella diameter, with no differences between treatment groups. PAR intensity primarily drove aerobic respiration and photosynthesis, with reduced PAR enhancing ETS activity and chlorophyll-a concentration, while UVA had less effect. ETS activity was positively correlated with chlorophyll-a concentration but negatively with jellyfish size. Both high PAR and high UVA exposure increased lipid peroxidation (LPO), with the highest levels under combined high PAR and UVA. These findings show that UVA does not directly affect photosynthesis but might enhances oxidative stress when combined with high PAR, increasing LPO. Despite oxidative stress, jellyfish showed consistent growth and normal morphology, highlighting their resilience to varying light. Color changes linked to PAR exposure indicated shifts in algal symbiont density. This study highlights the adaptive capacity of C. andromeda jellyfish to fluctuating light, emphasizing PAR’s role in regulating metabolism and oxidative stress. It also offers new insights into UVA’s underexplored impact on jellyfish physiology, paving the way for future research on UVA’s broader effects on marine invertebrates.